The development of stochastic SIR-SI Age-Structured model for leptospirosis mapping in Malaysia - Aznida Che Awang (2018)
This study aimed to develop the stochastic SIR-SI Age-Structured model to estimate therelative risk for leptospirosis mapping specifically for children and adults in Malaysia.This study used model development as it research design. The methodology of this study took intoaccount the transmission of leptospirosis in the stochastic SIR-SI model (S=susceptible, I=infected, R=recovered for human populations and S=susceptible, I=infected for vector populations). In this study, the existing SIR-SI model was improvised andadapted to the leptospirosis transmission. Then, the model was expended to form an alternativeSIR-SI Age-Structured model specifically for children and adults to estimate the relative risk ofleptospirosis for these populations in Malaysia. The data used in this study were weekly data fromepidemiology week 1 to epidemiology week 52 for the year 2015 for all sixteen states in Malaysia.The results of the analysis based on the age structured model were also compared with the existingmodels to identify the better model for estimating relative risk. For the children group, theresults showed that children in Kelantan have the highest risk of contracting leptospirosiswhile the children in Labuan have the lowest risk of contracting the disease. Similarly, adultsin Kelantan and Labuan also possessed the highest and lowest risk of contractingleptospirosis, respectively. As a conclusion, the new model was better as compared to otherexisting models in estimating relative risk for leptospirosis because it consideredimportant elements such as the number of population, age group and the transmission process of thedisease. This model also generates leptospirosis risk map for children and adults inMalaysia. In implication, the proposed model and generated risk maps can be practically appliedtowards the control of leptospirosis by government agencies, medical officers and authorities aswell as increasing the awareness of local communities towards the high-lowrisk areas of leptospirosis.